Carbon-based magnetic aerogel / graphene chinlon composite fabric as well as preparation method and application thereof
By preparing carbon-based magnetic aerogel/graphene nylon composite fabric, the problem of insufficient resistance to high-frequency electromagnetic interference of existing electromagnetic shielding materials is solved, and the lightweight and high-performance electromagnetic shielding effect is achieved.
Patent Information
- Application Number
- CN202510051948.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-14
- Publication Date
- 2025-04-11
- Estimated Expiration
- 2045-01-14
AI Technical Summary
When existing electromagnetic shielding materials face high-frequency, broadband and high-frequency electromagnetic interference, their anti-interference capabilities are insufficient, and traditional metal materials have high density and high mass, which limits their application.
Carbon-based magnetic aerogel/graphene nylon composite fabric was used to hydrothermal reactions by hydrothermal reactions of electromagnetic shielding fabric, graphene dispersion, dopamine hydrochloride solution and iron tetraoxide precursor solution to form a carbon-based magnetic hydrogel containing fabric, and cured by freeze-drying and water-based polyurethane to prepare a carbon-based magnetic aerogel/graphene nylon composite fabric.
This material is not only light in weight, but also has excellent anti-electromagnetic interference ability. Its electromagnetic shielding efficiency reaches 36.4~48.3dB at high frequency points, far exceeding the application standards of civilian electromagnetic shielding materials.
Smart Images

Figure CN119800699A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of electromagnetic shielding materials, and in particular to a carbon-based magnetic aerogel / graphene nylon composite fabric and a preparation method and application thereof. Background Art
[0002] As highly integrated and intelligent electronic and electrical equipment gradually pour into the fields of communications, electrical appliances, and transportation, electromagnetic technology has brought great convenience to people's lives, but it has also brought a lot of electromagnetic radiation, leading to electromagnetic pollution. It is imperative to develop materials with electromagnetic shielding properties. Electromagnetic shielding materials can absorb, reflect, and reduce energy consumption of external interference electromagnetic waves and internal electromagnetic waves. Therefore, electromagnetic shielding materials have a certain function of weakening interference for electronic and power equipment. Metal materials, as the longest-used and most widely used type of electromagnetic shielding materials, have the characteristics of strong stability, high mechanical properties, and excellent shielding effectiveness. However, with the continuous improvement of power supply equipment, especially switching power supplies, switching frequencies, and switching speeds, the requirements for electromagnetic shielding are becoming more and more stringent. The anti-electromagnetic interference capabilities of ordinary electromagnetic shielding materials or shielding bodies cannot meet this increasingly stringent application demand. At the same time, the advent of the 5G era requires shielding materials to be miniaturized, lightweight, broadband, and high-frequency, while the disadvantages of traditional metal materials, such as high density, high mass, and narrow shielding frequency band, limit their application. The current market demand for electromagnetic shielding materials is that the electromagnetic shielding performance of traditional materials can no longer meet people's needs, which also requires the advancement of electromagnetic shielding materials towards light weight and high performance.
[0003] Therefore, how to provide an electromagnetic shielding material that is lightweight and has excellent anti-electromagnetic interference capability has become a technical problem that needs to be urgently solved in this field. Summary of the invention
[0004] The purpose of the present invention is to provide a carbon-based magnetic aerogel / graphene nylon composite fabric and a preparation method and application thereof. The carbon-based magnetic aerogel / graphene nylon composite fabric prepared by the preparation method provided by the present invention is not only light in weight, but also has excellent anti-electromagnetic interference capability.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a carbon-based magnetic aerogel / graphene nylon composite fabric, comprising the following steps:
[0007] (1) mixing an electromagnetic shielding fabric, a graphene dispersion, a dopamine hydrochloride solution and a ferroferric oxide precursor solution, and then performing a hydrothermal reaction to obtain a carbon-based magnetic hydrogel containing the fabric; the electromagnetic shielding fabric is an electromagnetic shielding three-dimensional fabric or an electromagnetic shielding honeycomb fabric;
[0008] (2) freeze-drying the carbon-based magnetic hydrogel containing fabric obtained in step (1) to obtain a carbon-based magnetic aerogel composite fabric;
[0009] (3) The carbon-based magnetic aerogel composite fabric obtained in step (2) is mixed with an aqueous polyurethane solution and then cured to obtain a carbon-based magnetic aerogel / graphene nylon composite fabric.
[0010] Preferably, when the electromagnetic shielding fabric in step (1) is an electromagnetic shielding three-dimensional fabric, the three-dimensional structure of the electromagnetic shielding three-dimensional fabric is through-orthogonal, layered orthogonal, through-angular interlocking or layered angular interlocking.
[0011] Preferably, the electromagnetic shielding fabric in step (1) is woven from graphene nylon filaments; the specification of the graphene nylon filaments is 300D / 144F.
[0012] Preferably, in step (1), the mass ratio of graphene oxide in the graphene oxide dispersion to dopamine hydrochloride in the dopamine hydrochloride solution is 1:(0.5-2).
[0013] Preferably, in the step (1), the mass ratio of graphene oxide in the graphene oxide dispersion to the mass ratio of ferric chloride to ferrous chloride in the ferrosoferric oxide precursor solution is 2:4:2.
[0014] Preferably, the temperature of the hydrothermal reaction in step (1) is 70 to 80° C., and the time of the hydrothermal reaction is 12 to 20 hours.
[0015] Preferably, the viscosity of the aqueous polyurethane solution in step (3) is less than 300 mPa·S.
[0016] Preferably, the curing temperature in step (3) is 60 to 90° C., and the curing time is 6 to 8 hours.
[0017] The present invention provides a carbon-based magnetic aerogel / graphene nylon composite fabric prepared by the preparation method described in the above technical solution.
[0018] The present invention provides application of the carbon-based magnetic aerogel / graphene nylon composite fabric described in the above technical solution in electronic equipment.
[0019] The present invention provides a method for preparing a carbon-based magnetic aerogel / graphene nylon composite fabric, comprising the following steps: (1) mixing an electromagnetic shielding fabric, a graphene dispersion, a dopamine hydrochloride solution and a ferroferric oxide precursor solution, and then performing a hydrothermal reaction to obtain a carbon-based magnetic hydrogel containing the fabric; the electromagnetic shielding fabric is an electromagnetic shielding three-dimensional fabric or an electromagnetic shielding honeycomb fabric; (2) freeze-drying the carbon-based magnetic hydrogel containing the fabric obtained in the step (1) to obtain a carbon-based magnetic aerogel composite fabric; and (3) mixing the carbon-based magnetic aerogel composite fabric obtained in the step (2) with an aqueous polyurethane solution and then curing the mixture to obtain a carbon-based magnetic aerogel / graphene nylon composite fabric. The structure of the electromagnetic shielding fabric used in the present invention is a three-dimensional fabric or a honeycomb structure, wherein the three-dimensional fabric is a warp and weft yarn with conductive properties that are complexly interwoven according to its own organizational structure, so that the fabric layers are closely arranged, forming complex and diverse conductive network paths in the warp and weft directions as well as in the thickness direction. When electromagnetic waves are incident, they are absorbed and lost inside the fabric; and the honeycomb fabric is a "square pyramid" structure formed by the honeycomb structure, which can cause electromagnetic waves to be refracted multiple times therein and thus absorbed and lost; aerogel is a graphene hydrogel with a three-dimensional structure that is made of a reducing agent, dopamine, to grow Fe3O4 magnetic particles in situ, thereby The effective hybridization of carbon materials and nano-magnetic fillers is achieved. The fabric is freeze-dried together with the magnetic hydrogel, and the adhesion effect of dopamine is used to combine the electromagnetic shielding fabric with the aerogel. The aerogel part is composed of graphene and magnetic materials. Due to the three-dimensional porous structure of the aerogel itself, electromagnetic waves will be reflected and refracted multiple times inside it, thereby achieving a reduction effect. At the same time, the magnetic loss mechanism provided by the magnetic material further improves the electromagnetic shielding ability of the aerogel. Finally, it is coated and reinforced with aqueous polyurethane to improve the overall bonding strength of the carbon-based magnetic aerogel / graphene nylon composite fabric and ensure the softness of the composite fabric. The results of the embodiment show that the carbon-based magnetic aerogel / graphene nylon composite fabric prepared by the preparation method provided by the present invention is subjected to an electromagnetic shielding effectiveness test according to the window method described in GJB6190-2008 "Measurement Method for Shielding Effectiveness of Electromagnetic Shielding Materials". It is found that the electromagnetic shielding effectiveness of the carbon-based magnetic aerogel / graphene nylon composite fabric is 36.4-48.3 dB at high frequencies, which means that the fabric has a certain electromagnetic shielding effectiveness, far exceeding the GB T26667-2011 application standard for civil electromagnetic shielding materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 This is a machine drawing of electromagnetic shielding three-dimensional fabric;
[0021] Figure 2 This is a picture of electromagnetic shielding honeycomb fabric on the machine;
[0022] Figure 3 The three-dimensional structure is a tissue diagram of an electromagnetic shielding three-dimensional fabric with orthogonal penetration;
[0023] Figure 4 The organization diagram of the electromagnetic shielding three-dimensional fabric with a three-dimensional structure of layered orthogonal;
[0024] Figure 5 The three-dimensional structure is a tissue diagram of an electromagnetic shielding three-dimensional fabric with interlocking through corners;
[0025] Figure 6 A tissue diagram of an electromagnetic shielding three-dimensional fabric having a three-dimensional structure of layered angle interlocking;
[0026] Figure 7 is a radial cross-sectional view of a three-dimensional electromagnetic shielding fabric having a three-dimensional structure that is orthogonal throughout;
[0027] Figure 8 The radial cross-section diagram of the electromagnetic shielding three-dimensional fabric with a layered orthogonal three-dimensional structure;
[0028] Fig. 9 is a radial cross-sectional view of an electromagnetic shielding three-dimensional fabric having a three-dimensional structure and interlocking through corners;
[0029] Fig.10 A radial cross-sectional view of an electromagnetic shielding three-dimensional fabric having a three-dimensional structure of layered angle interlocking;
[0030] Fig.11 The tensile breaking strength test diagrams of four three-dimensional fabrics and honeycomb fabrics;
[0031] Fig.12 The actual pictures of the carbon-based hydrogels obtained in Test Examples 1 to 6;
[0032] Fig.13 This is a SEM image of the carbon-based aerogel prepared in Test Example 7;
[0033] Fig.14 This is a SEM image of the carbon-based aerogel prepared in Test Example 8;
[0034] Fig.15 This is a SEM image of the carbon-based aerogel prepared in Test Example 9;
[0035] Fig.16 This is a SEM image of the carbon-based aerogel prepared in Test Example 10;
[0036] Fig.17 SEM images of the carbon-based magnetic aerogels prepared in Test Examples 11 to 13;
[0037] Fig.18 This is an electron microscope image of the carbon-based magnetic aerogel / graphene nylon composite fabric prepared in Example 1. DETAILED DESCRIPTION
[0038] The present invention provides a method for preparing a carbon-based magnetic aerogel / graphene nylon composite fabric, comprising the following steps:
[0039] (1) mixing an electromagnetic shielding fabric, a graphene dispersion, a dopamine hydrochloride solution and a ferroferric oxide precursor solution, and then performing a hydrothermal reaction to obtain a carbon-based magnetic hydrogel containing the fabric; the electromagnetic shielding fabric is an electromagnetic shielding three-dimensional fabric or an electromagnetic shielding honeycomb fabric;
[0040] (2) freeze-drying the carbon-based magnetic hydrogel containing fabric obtained in step (1) to obtain a carbon-based magnetic aerogel composite fabric;
[0041] (3) The carbon-based magnetic aerogel composite fabric obtained in step (2) is mixed with an aqueous polyurethane solution and then cured to obtain a carbon-based magnetic aerogel / graphene nylon composite fabric.
[0042] In the present invention, unless otherwise specified, the raw materials used are commercially available products well known to those skilled in the art.
[0043] The present invention mixes electromagnetic shielding fabric, graphene dispersion, dopamine hydrochloride solution and ferroferric oxide precursor solution, and then performs hydrothermal reaction to obtain carbon-based magnetic hydrogel containing fabric; the electromagnetic shielding fabric is electromagnetic shielding three-dimensional fabric or electromagnetic shielding honeycomb fabric.
[0044] In the present invention, the electromagnetic shielding fabric is an electromagnetic shielding three-dimensional fabric or an electromagnetic shielding honeycomb fabric; the electromagnetic shielding fabric is preferably woven from graphene nylon filaments; the specification of the graphene nylon filaments is preferably 300D / 144F. In the present invention, the electromagnetic shielding three-dimensional fabric is shown in the figure. Figure 1 As shown; the electromagnetic shielding honeycomb fabric is shown in the machine diagram Figure 2 shown.
[0045] In the present invention, when the electromagnetic shielding fabric is an electromagnetic shielding three-dimensional fabric, the three-dimensional structure of the electromagnetic shielding three-dimensional fabric is preferably orthogonal through-intersection, orthogonal through-intersection, angular interlocking through-intersection or angular interlocking through-intersection. In the present invention, the three-dimensional structure is an electromagnetic shielding three-dimensional fabric with orthogonal through-intersection, as shown in the organization diagram Figure 3 As shown; the three-dimensional structure is a layered orthogonal electromagnetic shielding three-dimensional fabric organization diagram as shown Figure 4 The three-dimensional structure is an electromagnetic shielding three-dimensional fabric interlocked through the corners. Figure 5 The three-dimensional structure is a layered angle interlocked electromagnetic shielding three-dimensional fabric organization diagram as shown Figure 6 The three-dimensional structure is a radial cross-sectional view of the electromagnetic shielding three-dimensional fabric that penetrates the orthogonal Figure 7The three-dimensional structure is a radial cross-sectional view of a layered orthogonal electromagnetic shielding three-dimensional fabric as shown in Figure 8 The three-dimensional structure is a radial cross-sectional view of an electromagnetic shielding three-dimensional fabric interlocked with corners as shown in Fig. 9 The three-dimensional structure is a radial cross-sectional view of a layered angle interlocked electromagnetic shielding three-dimensional fabric as shown Fig.10 shown.
[0046] In the present invention, the preparation method of the electromagnetic shielding three-dimensional fabric preferably includes: tightly winding graphene nylon filaments of 40 to 60 m in length on the bobbin respectively, ensuring that one graphene nylon filament is wound around one bobbin, and then passing through the threading holes in sequence according to the order of the bobbins, waiting for drawing in the heald; drawing in the heald and reeding according to the three-dimensional structure of the electromagnetic shielding three-dimensional fabric, passing the graphene nylon filaments through the heald eyes in sequence according to the designed drawing in the heald method and passing through the steel reed eyes with a specification of 5 reeds / entry, fixing all the warp yarns, and then inserting and beating the weft according to the arrangement of the warp and weft yarns, completing the weaving, and obtaining the electromagnetic shielding three-dimensional fabric. The present invention has no special limitation on the number of the graphene nylon filaments, and can be controlled according to the size of the required electromagnetic shielding three-dimensional fabric. As an embodiment of the present invention, the length of the graphene nylon filament can be 50 m; the number of the graphene nylon filaments can be 100 to 500, and can also be 200 to 400.
[0047] In the present invention, when the electromagnetic shielding fabric is an electromagnetic shielding honeycomb fabric, the preparation method of the electromagnetic shielding honeycomb fabric preferably includes: arranging graphene nylon filaments of 40 to 60 m in length tightly and neatly on a sample loom; drawing in and reeding according to the structure of the electromagnetic shielding honeycomb fabric, passing the graphene nylon filaments through the heald eyes in sequence according to the designed drawing in method and passing through the steel reed eyes with a specification of 5 reeds / insertion, fixing all the warp yarns, and then inserting and beating the weft according to the arrangement of the warp and weft yarns, completing the weaving, and obtaining the electromagnetic shielding honeycomb fabric. The present invention has no special limitation on the number of the graphene nylon filaments, and it can be controlled according to the size of the required electromagnetic shielding honeycomb fabric. As an embodiment of the present invention, the length of the graphene nylon filaments can be 50 m; the number of the graphene nylon filaments can be 100 to 500, and can also be 200 to 400.
[0048] The present invention has no special limitation on the specific size of the electromagnetic shielding fabric, and it can be prepared according to the size of the required carbon-based magnetic aerogel / graphene nylon composite fabric. As an embodiment of the present invention, the length of the electromagnetic shielding fabric is preferably 6 to 12 cm, more preferably 8 to 10 cm; the width of the electromagnetic shielding fabric is preferably 6 to 12 cm, more preferably 8 to 10 cm.
[0049] In the present invention, the concentration of the graphene oxide dispersion is preferably 1 to 3 mg / mL, more preferably 2 mg / mL. In the present invention, the method for preparing the graphene oxide dispersion preferably includes mixing graphene oxide and water to obtain a graphene oxide dispersion. In the present invention, the water is preferably distilled water. In the present invention, the way of mixing the graphene oxide and water is preferably ultrasonic mixing; the temperature of the ultrasonic mixing is preferably 20 to 30°C, more preferably 25°C; the time of the ultrasonic mixing is preferably 0.5 to 2h, more preferably 1h; the ultrasonic frequency of the ultrasonic mixing is preferably 30 to 50kHz, more preferably 40kHz; the ultrasonic mixing is preferably carried out in an ultrasonic cleaning machine.
[0050] In the present invention, the concentration of the dopamine hydrochloride solution is preferably 1 to 6 mg / mL, more preferably 2 to 5 mg / mL, and further preferably 3 to 4 mg / mL. In the present invention, the method for preparing the dopamine hydrochloride solution preferably includes mixing dopamine hydrochloride and water to obtain a dopamine hydrochloride solution. In the present invention, the water is preferably distilled water. In the present invention, the method for mixing dopamine hydrochloride and water is preferably magnetic stirring; the temperature of the magnetic stirring is preferably 50 to 70°C, more preferably 60°C; the time of the magnetic stirring is preferably 1 to 4h, more preferably 2 to 3h; the speed of the magnetic stirring is preferably 700 to 1000r / min, more preferably 800 to 900r / min; the magnetic stirring is preferably carried out on a magnetic stirrer.
[0051] In the present invention, the method for preparing the ferroferric oxide precursor solution is preferably to mix the ferric chloride solution and the ferrous chloride solution, and then magnetically stir, and then ultrasonically mix, to obtain the ferroferric oxide precursor solution. In the present invention, the temperature of the magnetic stirring is preferably room temperature; the time of the magnetic stirring is preferably 18 to 24 hours, and more preferably 20 to 22 hours; the speed of the magnetic stirring is preferably 700 to 800 r / min; the magnetic stirring is preferably carried out on a magnetic stirrer; the temperature of the ultrasonic mixing is preferably 20 to 30°C, and more preferably 25°C; the time of the ultrasonic mixing is preferably 0.5 to 2 hours, and more preferably 1 to 1.5 hours; the ultrasonic frequency of the ultrasonic mixing is preferably 30 to 40kHz, and more preferably 35kHz; the ultrasonic mixing is preferably carried out in an ultrasonic cleaning machine.
[0052] In the present invention, the method for preparing the ferric chloride solution is preferably to mix ferric chloride and water to obtain the ferric chloride solution. In the present invention, the water is preferably distilled water. In the present invention, the method for mixing the ferric chloride and water is preferably magnetic stirring; the temperature of the magnetic stirring is preferably 40 to 60°C, more preferably 50°C; the time of the magnetic stirring is preferably 10 to 30 minutes, more preferably 20 minutes; the speed of the magnetic stirring is preferably 400 to 600 r / min, more preferably 500 r / min; the magnetic stirring is preferably performed on a magnetic stirrer.
[0053] In the present invention, the method for preparing the ferrous chloride solution is preferably to mix ferrous chloride and water to obtain the ferrous chloride solution. In the present invention, the water is preferably distilled water. In the present invention, the method for mixing the ferrous chloride and water is preferably magnetic stirring; the temperature of the magnetic stirring is preferably 20 to 40°C, more preferably 30°C; the time of the magnetic stirring is preferably 10 to 30 minutes, more preferably 20 minutes; the speed of the magnetic stirring is preferably 600 to 1000 r / min, more preferably 800 r / min; the magnetic stirring is preferably performed on a magnetic stirrer.
[0054] In the present invention, the concentration of the ferric chloride solution is preferably 2-6 mg / mL, more preferably 3-5 mg / mL, and further preferably 4 mg / mL; the concentration of the ferrous chloride solution is preferably 1-3 mg / mL, and more preferably 2 mg / mL.
[0055] In the present invention, the mass ratio of graphene oxide in the graphene oxide dispersion and the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is preferably 2:4:2. By controlling the mass ratio of graphene oxide, ferric chloride and ferrous chloride, the particle size distribution in the carbon-based magnetic aerogel can be made relatively dispersed and uniform.
[0056] In the present invention, the volume ratio of the mass of the electromagnetic shielding fabric, the volume of the graphene dispersion, the volume of the dopamine hydrochloride solution and the ferroferric oxide precursor solution is preferably (10-20) g: (10-60) mL: (5-40) mL: (30-100) mL, more preferably (12-18) g: (15-40) mL: (10-30) mL: (35-80) mL, and further preferably (14-16) g: (20-30) mL: (20-30) mL: (40-60) mL.
[0057] In the present invention, the mass ratio of graphene oxide in the graphene oxide dispersion to dopamine hydrochloride in the dopamine hydrochloride solution is preferably 1:(0.5-2), more preferably 1:(1-1.5). The present invention can facilitate the subsequent formation of hydrogel by controlling the dosage relationship of the two.
[0058] In the present invention, the electromagnetic shielding fabric, graphene dispersion, dopamine hydrochloride solution and ferroferric oxide precursor solution are preferably mixed in the following manner: firstly, the electromagnetic shielding fabric is placed in the graphene dispersion for ultrasonic mixing, and then the dopamine hydrochloride solution and ferroferric oxide precursor solution are added. The present invention has no special limitation on the ultrasonic power and ultrasonic time of the ultrasonic mixing, which can be determined according to the technical common sense of those skilled in the art, so that the electromagnetic shielding fabric can be completely and evenly impregnated with the graphene dispersion.
[0059] In the present invention, the temperature of the hydrothermal reaction is preferably 70-80°C, more preferably 75°C; the time of the hydrothermal reaction is preferably 12-20 hours, more preferably 16 hours; the hydrothermal reaction is preferably carried out in a blast drying oven. The present invention controls the temperature and time of the hydrothermal reaction to polymerize the aqueous solution containing the electromagnetic shielding fabric and the magnetic material under a hot pressure environment to form a graphene hydrogel containing the electromagnetic shielding fabric and the magnetic particles.
[0060] After obtaining the carbon-based magnetic hydrogel containing fabric, the present invention freeze-dries the carbon-based magnetic hydrogel containing fabric to obtain the carbon-based magnetic aerogel composite fabric.
[0061] In the present invention, the carbon-based magnetic hydrogel containing the fabric is preferably firstly subjected to pH adjustment and washing, and then freeze-dried.
[0062] In the present invention, the method of adjusting the pH value is preferably to add ammonia water. The present invention has no special limitation on the concentration and dosage of the ammonia water, and it is sufficient to ensure that the pH value of the carbon-based magnetic hydrogel containing the fabric meets the requirements. The present invention has no special limitation on the method of adding the ammonia water, and it can be determined according to the technical common sense of those skilled in the art. As an embodiment of the present invention, the ammonia water can be added dropwise; the pH value of the carbon-based magnetic hydrogel containing the fabric after adding the ammonia water can be 9.
[0063] In the present invention, the washing is preferably performed using an ethanol solution. In the present invention, the ethanol solution is preferably an ethanol aqueous solution; the mass concentration of the ethanol solution is preferably 20%; the removal method of the ethanol solution during the washing is preferably extraction. The present invention has no special restrictions on the specific operation of the extraction, and the ethanol solution after washing can be removed. The present invention has no special restrictions on the number of washings, and the pH value of the solution can be made to reach 6 to 7. The present invention can remove impurities by washing.
[0064] In the present invention, the freeze drying is preferably performed by pre-freezing at -20°C for 72 hours and then freeze drying at -40°C for 48 to 72 hours. The freeze drying method is adopted in the present invention to avoid affecting the structure of the product.
[0065] After obtaining the carbon-based magnetic aerogel composite fabric, the present invention mixes the carbon-based magnetic aerogel composite fabric with an aqueous polyurethane solution and then solidifies the mixture to obtain the carbon-based magnetic aerogel / graphene nylon composite fabric.
[0066] In the present invention, the viscosity of the aqueous polyurethane solution is preferably less than 300 mPa·S, more preferably 150-280 mPa·S, and further preferably 200-250 mPa·S. In the present invention, the ratio of the mass of the electromagnetic shielding fabric to the volume of the aqueous polyurethane solution is preferably (10-20) g: (15-30) mL, more preferably (12-18) g: (20-25) mL, and further preferably (14-16) g: (20-25) mL. The present invention can ensure that a complete polyurethane film can be formed by controlling the amount of the aqueous polyurethane solution.
[0067] In the present invention, the reduced graphene oxide hydrogel fabric and the aqueous polyurethane solution are preferably mixed in such a way that the aqueous polyurethane solution is sprayed on the reduced graphene oxide hydrogel fabric. The present invention has no particular limitation on the specific operation of the spraying, and a spraying method well known to those skilled in the art can be used and the aqueous polyurethane solution can be sprayed evenly.
[0068] In the present invention, the curing temperature is preferably 60-90°C; the curing time is preferably 6-8h. The present invention can remove the solvent in the aqueous polyurethane solution by curing, thereby forming a polyurethane film on the reduced graphene oxide hydrogel fabric. As an embodiment of the present invention, the curing temperature can be 70-80°C; the curing time can be 7h.
[0069] The structure of the electromagnetic shielding fabric used in the present invention is a three-dimensional fabric or a honeycomb structure, wherein the three-dimensional fabric is a warp and weft yarn with conductive properties that are complexly interwoven according to its own organizational structure, so that the fabric layers are closely arranged, forming complex and diverse conductive network paths in the warp and weft directions as well as in the thickness direction. When electromagnetic waves are incident, they are absorbed and lost inside the fabric; and the honeycomb fabric is a "square pyramid" structure formed by the honeycomb structure, which can cause electromagnetic waves to be refracted multiple times therein and thus absorbed and lost; aerogel is a graphene hydrogel with a three-dimensional structure that is made of a reducing agent, dopamine, to grow Fe3O4 magnetic particles in situ, thereby The effective hybridization of carbon materials and nano-magnetic fillers is achieved. The fabric is freeze-dried together with the magnetic hydrogel, and the adhesion effect of dopamine is used to combine the electromagnetic shielding fabric with the aerogel. The aerogel part is composed of graphene and magnetic materials. Due to the three-dimensional porous structure of the aerogel itself, electromagnetic waves will be reflected and refracted multiple times inside it, thereby achieving a reduction effect. At the same time, the magnetic loss mechanism provided by the magnetic material further improves the electromagnetic shielding ability of the aerogel. Finally, it is coated and reinforced with aqueous polyurethane to improve the overall bonding strength of the carbon-based magnetic aerogel / graphene nylon composite fabric and ensure the softness of the composite fabric.
[0070] The present invention also provides a carbon-based magnetic aerogel / graphene nylon composite fabric prepared by the preparation method described in the above technical solution.
[0071] The present invention also provides the use of the carbon-based magnetic aerogel / graphene nylon composite fabric described in the above technical solution in electronic equipment.
[0072] The present invention has no special limitation on the specific operation of the application, and the application can be performed in a manner well known to those skilled in the art.
[0073] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0074] The selection method of the electromagnetic shielding fabric in the embodiment is as follows:
[0075] ① The preparation method of the electromagnetic shielding three-dimensional fabric with a three-dimensional structure of penetrating orthogonal is as follows: 200 graphene nylon filaments with a length of 50m are tightly wound on 200 bobbins respectively, ensuring that one graphene nylon filament is wound around one bobbin, and then pass through the threading holes in sequence according to the order of the bobbins to be drawn into the reed; according to the three-dimensional structure of the electromagnetic shielding three-dimensional fabric, the 200 graphene nylon filaments are passed through the heald eyes in sequence according to the designed drawing method and passed through the steel reed eyes at a specification of 5 reeds / insertion, all the warp yarns are fixed, and then the weft is inserted and beaten according to the arrangement of the warp and weft yarns to complete the weaving, and a three-dimensional electromagnetic shielding three-dimensional fabric with a length of 10cm and a width of 10cm and a penetrating orthogonal structure is obtained;
[0076] ② The preparation method of the electromagnetic shielding three-dimensional fabric with a layered orthogonal three-dimensional structure is as follows: 200 graphene nylon filaments with a length of 50m are tightly wound on 200 bobbins respectively, ensuring that one graphene nylon filament is wound around one bobbin, and then pass through the threading holes in sequence according to the order of the bobbins to be drawn into the reed; according to the three-dimensional structure of the electromagnetic shielding three-dimensional fabric, the 200 graphene nylon filaments are passed through the heald eyes in sequence according to the designed drawing method and passed through the steel reed eyes at a specification of 5 reeds / insertion, all the warp yarns are fixed, and then the weft is inserted and beaten according to the arrangement of the warp and weft yarns to complete the weaving, and a three-dimensional electromagnetic shielding three-dimensional fabric with a length of 10cm and a width of 10cm and a layered orthogonal structure is obtained;
[0077] ③ The preparation method of the electromagnetic shielding three-dimensional fabric with a three-dimensional structure of penetrating corner interlocking is as follows: 200 graphene nylon filaments with a length of 50m are tightly wound on 200 bobbins respectively, ensuring that one graphene nylon filament is wound around one bobbin, and then pass through the threading holes in sequence according to the order of the bobbins to be drawn into the reed; according to the three-dimensional structure of the electromagnetic shielding three-dimensional fabric, the heddle and reed are drawn in sequence, and 200 graphene nylon filaments are passed through the heddle eyes in sequence according to the designed heddle drawing method and passed through the steel reed eyes at a specification of 5 reeds / insertion, all the warp yarns are fixed, and then the weft is inserted and beaten according to the arrangement of the warp and weft yarns to complete the weaving, and a three-dimensional structure of electromagnetic shielding three-dimensional fabric with a length of 10cm and a width of 10cm and a penetrating corner interlocking is obtained;
[0078] ④ The preparation method of the electromagnetic shielding three-dimensional fabric with a three-dimensional structure of layered angular interlocking is as follows: 200 graphene nylon filaments with a length of 50m are tightly wound on 200 bobbins respectively, ensuring that one graphene nylon filament is wound around one bobbin, and then pass through the threading holes in sequence according to the order of the bobbins to be drawn into the reed; according to the three-dimensional structure of the electromagnetic shielding three-dimensional fabric, the heddle and reed are drawn in sequence, and 200 graphene nylon filaments are passed through the heddle eyes in sequence according to the designed heddle drawing method and passed through the steel reed eyes at a specification of 5 reeds / insertion, all the warp yarns are fixed, and then the weft is inserted and beaten according to the arrangement of the warp and weft yarns to complete the weaving, and a three-dimensional electromagnetic shielding three-dimensional fabric with a length of 10cm and a width of 10cm and a layered angular interlocking structure is obtained;
[0079] ⑤ When the electromagnetic shielding fabric is an electromagnetic shielding honeycomb fabric, the preparation method of the electromagnetic shielding honeycomb fabric is: 200 graphene nylon filaments with a length of 50m are tightly and neatly arranged on a small sample loom; according to the structure of the electromagnetic shielding honeycomb fabric, the healds and reeds are drawn in sequence, and the 200 graphene nylon filaments are passed through the heald eyes in sequence according to the designed heald drawing method and passed through the reed eyes at a specification of 5 reeds / insertion, all the warp yarns are fixed, and then the weft is inserted and beaten according to the arrangement of the warp and weft yarns to complete the weaving, and an electromagnetic shielding honeycomb fabric with a length of 10cm and a width of 10cm is obtained;
[0080] The specification of the graphene nylon filament used in the above preparation is 300D / 144F.
[0081] The basic characterization of the above four three-dimensional fabrics and honeycomb fabrics was measured, including warp density, weft density, and size. The basic information of the electromagnetic shielding fabrics is shown in Table 1:
[0082] Table 1 Basic information of electromagnetic shielding fabrics
[0083] Sample Size (cm) Warp density (root / 10cm) Weft density (root / 10cm) Orthogonal 10×10 200 190 Layered Orthogonal 10×10 200 195 Through-angle interlocking 10×10 200 192 Layered corner interlocking 10×10 200 189 honeycomb 10×10 200 192
[0084] According to the method described in GB / T 3923.1-2013 "Tensile Properties of Textile Fabrics", four three-dimensional fabrics and honeycomb fabrics were tested for tensile breaking strength. The results are as follows: Fig.11 As shown. Fig.11 It can be seen that the breaking strength of the layered corner interlock is greater than 250N, and the mechanical properties are the best.
[0085] The shielding room window method was used to test the shielding effectiveness of four three-dimensional fabrics and honeycomb fabrics against electromagnetic waves at six frequencies: 30MHz, 450MHz, 1GHz, 5GHz, 10GHz, and 188GHz. The test results are shown in Table 2:
[0086] Table 2 Shielding effectiveness of electromagnetic shielding fabrics
[0087] Sample Layered Orthogonal Orthogonal Layered Angle Chain Through-angle interlocking plain weave 30MHz 8 6 9 6 2 450MHz 10 10 15 8 4 1GHz 14 10 14 7 3 5GHz 7 5 8 9 6 10GHz 7 6 9 7 5 18GHz 8 7 21 5 6
[0088] As can be seen from Table 2, the shielding effectiveness of layered angle interlocking is the best at both high and low frequencies, especially at 18GHz, which has exceeded the 20dB application standard of GBT26667-2011 for civil electromagnetic shielding materials. In order to unify the variables, the warp and weft densities of the five fabrics are unified. The reason for the difference in electromagnetic shielding effectiveness is that the fabric structure of the five fabrics is different. From the radial profile of the fabric, the weft yarns and warp yarns of the layered angle interlocking are interwoven at an angle of 45°. When the electromagnetic wave passes through the fabric at a vertical angle of 90°, more energy is blocked on the fabric surface, thereby achieving the electromagnetic shielding capability. At the same time, compared with other fabrics, the layered angle interlocking has more interlacing points of warp and weft yarns, so that the warp and weft yarns form an intricate and intertwined conductive path, and the electromagnetic shielding capability is better. Therefore, when the three-dimensional organization of the electromagnetic shielding fabric is layered angle interlocking, the electromagnetic shielding effect is the best.
[0089] In summary, an electromagnetic shielding fabric with a three-dimensional structure of layered angle interlocking was selected to prepare carbon-based magnetic aerogel / graphene nylon composite fabric.
[0090] Example 1
[0091] A method for preparing a carbon-based magnetic aerogel / graphene nylon composite fabric is as follows:
[0092] (1) adding graphene oxide to distilled water, and then ultrasonically mixing in an ultrasonic cleaning machine to obtain a graphene oxide dispersion; the ultrasonic mixing temperature is 25° C., the ultrasonic mixing time is 1 h, and the ultrasonic mixing frequency is 40 kHz;
[0093] (2) adding dopamine hydrochloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a dopamine hydrochloride solution; the magnetic stirring temperature is 60° C., the magnetic stirring time is 2 h, and the magnetic stirring speed is 800 r / min;
[0094] (3) adding ferric chloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a ferric chloride solution; the temperature of the magnetic stirring is 50° C., the time of the magnetic stirring is 20 min, and the speed of the magnetic stirring is 500 r / min; the concentration of the ferric chloride solution is 4 mg / mL;
[0095] (4) adding ferrous chloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a ferrous chloride solution; the temperature of the magnetic stirring is 30° C., the time of the magnetic stirring is 20 min, and the speed of the magnetic stirring is 800 r / min; the concentration of the ferrous chloride solution is 2 mg / mL;
[0096] (5) mixing the ferric chloride solution obtained in step (3) and the ferrous chloride solution obtained in step (4), first performing magnetic stirring on a magnetic stirrer, and then performing ultrasonic mixing in an ultrasonic cleaning machine to obtain a ferroferric oxide precursor solution; the temperature of the magnetic stirring is room temperature, the time of the magnetic stirring is 20 hours, and the speed of the magnetic stirring is 800 r / min; the temperature of the ultrasonic mixing is 25° C., the time of the ultrasonic mixing is 1 hour, and the ultrasonic frequency of the ultrasonic mixing is 35 kHz; the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is 2:1;
[0097] (6) First, the electromagnetic shielding fabric is placed in the graphene dispersion for ultrasonic mixing, and then the dopamine hydrochloride solution and the ferroferric oxide precursor solution are added, and then the fabric is placed in a blast drying oven for hydrothermal reaction at 75°C for 16 hours to obtain a carbon-based magnetic hydrogel containing the fabric; the electromagnetic shielding fabric is the electromagnetic shielding fabric with a layered angle interlocking three-dimensional structure prepared above; the length of the electromagnetic shielding fabric is 10 cm, the width is 10 cm, and the mass of the electromagnetic shielding fabric is 15.8 g; the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 2 mg / mL; the mass ratio of the graphene oxide in the graphene oxide dispersion to the dopamine hydrochloride in the dopamine hydrochloride solution is 1:1; the amount of the ferroferric oxide precursor solution is 40 mL, and the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is 2:1;
[0098] (7) adding ammonia water to the carbon-based magnetic hydrogel containing fabric obtained in step (6) until the pH value is 9, then washing with 20% ethanol aqueous solution until the pH value is 7, extracting the ethanol aqueous solution, and finally pre-freezing at -20°C for 72 hours, and freeze-drying at -40°C for 72 hours to obtain a carbon-based magnetic aerogel composite fabric;
[0099] (8) Spray 20 mL of the aqueous polyurethane solution on the reduced graphene oxide hydrogel fabric obtained in step (7), and then cure it at 80° C. for 8 h to obtain a carbon-based magnetic aerogel / graphene nylon composite fabric.
[0100] Test Example 1
[0101] 1) adding graphene oxide to distilled water, and then ultrasonically mixing in an ultrasonic cleaning machine to obtain a graphene oxide dispersion; the ultrasonic mixing temperature is 25° C., the ultrasonic mixing time is 1 h, and the ultrasonic mixing frequency is 40 kHz;
[0102] 2) adding dopamine hydrochloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a dopamine hydrochloride solution; the magnetic stirring temperature is 60° C., the magnetic stirring time is 2 h, and the magnetic stirring speed is 800 r / min;
[0103] 3) The graphene dispersion and the dopamine hydrochloride solution are mixed, and then placed in a forced air drying oven for hydrothermal reaction at 75° C. for 16 hours to obtain a carbon-based hydrogel; the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 1 mg / mL; the mass ratio of graphene oxide in the graphene oxide dispersion to dopamine hydrochloride in the dopamine hydrochloride solution is 1:0.5.
[0104] Test Example 2
[0105] In the step 3), the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 2 mg / mL; the mass ratio of the graphene oxide in the graphene oxide dispersion to the dopamine hydrochloride in the dopamine hydrochloride solution is 1:1;
[0106] The other conditions are the same as those in Test Example 1.
[0107] Test Example 3
[0108] In the step 3), the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 3 mg / mL; the mass ratio of the graphene oxide in the graphene oxide dispersion to the dopamine hydrochloride in the dopamine hydrochloride solution is 1:1.5;
[0109] The other conditions are the same as those in Test Example 1.
[0110] Test Example 4
[0111] In the step 3), the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 4 mg / mL; the mass ratio of the graphene oxide in the graphene oxide dispersion to the dopamine hydrochloride in the dopamine hydrochloride solution is 1:2;
[0112] The other conditions are the same as those in Test Example 1.
[0113] Test Example 5
[0114] In the step 3), the amount of graphene dispersion is 20 mL, and the concentration of graphene oxide dispersion is 2 mg / mL; the amount of dopamine hydrochloride solution is 20 mL, and the concentration of dopamine hydrochloride solution is 5 mg / mL; the mass ratio of graphene oxide in the graphene oxide dispersion to dopamine hydrochloride in the dopamine hydrochloride solution is 1:2.5;
[0115] The other conditions are the same as those in Test Example 1.
[0116] Test Example 6
[0117] In the step 3), the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 6 mg / mL; the mass ratio of the graphene oxide in the graphene oxide dispersion to the dopamine hydrochloride in the dopamine hydrochloride solution is 1:3;
[0118] The other conditions are the same as those in Test Example 1.
[0119] In order to explore the effect of the dosage relationship of graphene oxide and dopamine hydrochloride on the structure of carbon-based hydrogel, tests were conducted, namely test examples 1 to 6. The actual pictures of carbon-based hydrogels obtained in test examples 1 to 6 are as follows: Fig.12 shown. Fig.12 In the figure, #1 to #6 are the actual pictures of the carbon-based hydrogels prepared in test examples 1 to 6. Fig.12 It can be seen that with the increase of dopamine hydrochloride content in the carbon-based hydrogel, the appearance of the carbon-based hydrogel changes. When the mass ratio of graphene oxide and dopamine hydrochloride is less than 1:1, the appearance of the carbon-based hydrogel is irregular; when the mass ratio of graphene oxide and dopamine hydrochloride is greater than 1:2, the structure of the carbon-based hydrogel begins to collapse, and when it is 1:3, the hydrogel cannot be formed.
[0120] Test cases 7 to 10
[0121] Ammonia water was added to the carbon-based hydrogels obtained in Test Examples 1 to 4 to a pH value of 9, and then washed with an ethanol aqueous solution with a mass concentration of 20% to a pH value of 7, the ethanol aqueous solution was extracted, and finally pre-frozen at -20°C for 72h and freeze-dried at -40°C for 72h to obtain carbon-based aerogels, which are Test Examples 7 to 10, respectively.
[0122] The carbon-based aerogels prepared in Test Examples 7 to 10 were observed by scanning electron microscopy, and the obtained SEM images are as follows: Figures 13-16 As shown. Figures 13-16It can be seen that in the carbon-based aerogel prepared in Test Example 1, the aerogel has too large flakes and too few pores; in the carbon-based aerogel prepared in Test Example 3, the aerogel is agglomerated and piled; in the carbon-based aerogel prepared in Test Example 4, the aerogel is coated into balls, so the mass ratio of graphene oxide and dopamine hydrochloride is selected as 1:1 as the optimal value for the base aerogel loaded with Fe3O4 particles.
[0123] Test Example 11
[0124] (1) adding graphene oxide to distilled water, and then ultrasonically mixing in an ultrasonic cleaning machine to obtain a graphene oxide dispersion; the ultrasonic mixing temperature is 25° C., the ultrasonic mixing time is 1 h, and the ultrasonic mixing frequency is 40 kHz;
[0125] (2) adding dopamine hydrochloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a dopamine hydrochloride solution; the magnetic stirring temperature is 60° C., the magnetic stirring time is 2 h, and the magnetic stirring speed is 800 r / min;
[0126] (3) adding ferric chloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a ferric chloride solution; the temperature of the magnetic stirring is 50° C., the time of the magnetic stirring is 20 min, and the speed of the magnetic stirring is 500 r / min; the concentration of the ferric chloride solution is 2 mg / mL;
[0127] (4) adding ferrous chloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a ferrous chloride solution; the temperature of the magnetic stirring is 30° C., the time of the magnetic stirring is 20 min, and the speed of the magnetic stirring is 800 r / min; the concentration of the ferrous chloride solution is 1 mg / mL;
[0128] (5) mixing the ferric chloride solution obtained in step (3) and the ferrous chloride solution obtained in step (4), first performing magnetic stirring on a magnetic stirrer, and then performing ultrasonic mixing in an ultrasonic cleaning machine to obtain a ferroferric oxide precursor solution; the temperature of the magnetic stirring is room temperature, the time of the magnetic stirring is 20 hours, and the speed of the magnetic stirring is 800 r / min; the temperature of the ultrasonic mixing is 25° C., the time of the ultrasonic mixing is 1 hour, and the ultrasonic frequency of the ultrasonic mixing is 35 kHz; the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is 2:1;
[0129] (6) adding the dopamine hydrochloride solution obtained in step (2) and the ferroferric oxide precursor solution obtained in step (5) to the graphene dispersion obtained in step (1), and then placing the mixture in a forced air drying oven for hydrothermal reaction at 75° C. for 16 h to obtain a carbon-based magnetic hydrogel; the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 2 mg / mL; the amount of the ferroferric oxide precursor solution is 40 mL, and the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is 2:1;
[0130] (7) Ammonia water was added dropwise to the carbon-based magnetic hydrogel obtained in step (6) until the pH value was 9, and then washed with an ethanol aqueous solution with a mass concentration of 20% until the pH value was 7, the ethanol aqueous solution was extracted, and finally pre-frozen at -20°C for 72 hours and freeze-dried at -40°C for 72 hours to obtain a carbon-based magnetic aerogel.
[0131] Test Example 12
[0132] (1) adding graphene oxide to distilled water, and then ultrasonically mixing in an ultrasonic cleaning machine to obtain a graphene oxide dispersion; the ultrasonic mixing temperature is 25° C., the ultrasonic mixing time is 1 h, and the ultrasonic mixing frequency is 40 kHz;
[0133] (2) adding dopamine hydrochloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a dopamine hydrochloride solution; the magnetic stirring temperature is 60° C., the magnetic stirring time is 2 h, and the magnetic stirring speed is 800 r / min;
[0134] (3) adding ferric chloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a ferric chloride solution; the temperature of the magnetic stirring is 50° C., the time of the magnetic stirring is 20 min, and the speed of the magnetic stirring is 500 r / min; the concentration of the ferric chloride solution is 4 mg / mL;
[0135] (4) adding ferrous chloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a ferrous chloride solution; the temperature of the magnetic stirring is 30° C., the time of the magnetic stirring is 20 min, and the speed of the magnetic stirring is 800 r / min; the concentration of the ferrous chloride solution is 2 mg / mL;
[0136] (5) mixing the ferric chloride solution obtained in step (3) and the ferrous chloride solution obtained in step (4), first performing magnetic stirring on a magnetic stirrer, and then performing ultrasonic mixing in an ultrasonic cleaning machine to obtain a ferroferric oxide precursor solution; the temperature of the magnetic stirring is room temperature, the time of the magnetic stirring is 20 hours, and the speed of the magnetic stirring is 800 r / min; the temperature of the ultrasonic mixing is 25° C., the time of the ultrasonic mixing is 1 hour, and the ultrasonic frequency of the ultrasonic mixing is 35 kHz; the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is 2:1;
[0137] (6) adding the dopamine hydrochloride solution obtained in step (2) and the ferroferric oxide precursor solution obtained in step (5) to the graphene dispersion obtained in step (1), and then placing the mixture in a forced air drying oven for hydrothermal reaction at 75° C. for 16 h to obtain a carbon-based magnetic hydrogel; the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 2 mg / mL; the amount of the ferroferric oxide precursor solution is 40 mL, and the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is 2:1;
[0138] (7) Ammonia water was added dropwise to the carbon-based magnetic hydrogel obtained in step (6) until the pH value was 9, and then washed with an ethanol aqueous solution with a mass concentration of 20% until the pH value was 7, the ethanol aqueous solution was extracted, and finally pre-frozen at -20°C for 72 hours and freeze-dried at -40°C for 72 hours to obtain a carbon-based magnetic aerogel.
[0139] Test Example 13
[0140] (1) adding graphene oxide to distilled water, and then ultrasonically mixing in an ultrasonic cleaning machine to obtain a graphene oxide dispersion; the ultrasonic mixing temperature is 25° C., the ultrasonic mixing time is 1 h, and the ultrasonic mixing frequency is 40 kHz;
[0141] (2) adding dopamine hydrochloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a dopamine hydrochloride solution; the magnetic stirring temperature is 60° C., the magnetic stirring time is 2 h, and the magnetic stirring speed is 800 r / min;
[0142] (3) adding ferric chloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a ferric chloride solution; the temperature of the magnetic stirring is 50° C., the time of the magnetic stirring is 20 min, and the speed of the magnetic stirring is 500 r / min; the concentration of the ferric chloride solution is 6 mg / mL;
[0143] (4) adding ferrous chloride to distilled water, and then performing magnetic stirring on a magnetic stirrer to obtain a ferrous chloride solution; the temperature of the magnetic stirring is 30° C., the time of the magnetic stirring is 20 min, and the speed of the magnetic stirring is 800 r / min; the concentration of the ferrous chloride solution is 3 mg / mL;
[0144] (5) mixing the ferric chloride solution obtained in step (3) and the ferrous chloride solution obtained in step (4), first performing magnetic stirring on a magnetic stirrer, and then performing ultrasonic mixing in an ultrasonic cleaning machine to obtain a ferroferric oxide precursor solution; the temperature of the magnetic stirring is room temperature, the time of the magnetic stirring is 20 hours, and the speed of the magnetic stirring is 800 r / min; the temperature of the ultrasonic mixing is 25° C., the time of the ultrasonic mixing is 1 hour, and the ultrasonic frequency of the ultrasonic mixing is 35 kHz; the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is 2:1;
[0145] (6) adding the dopamine hydrochloride solution obtained in step (2) and the ferroferric oxide precursor solution obtained in step (5) to the graphene dispersion obtained in step (1), and then placing the mixture in a forced air drying oven for hydrothermal reaction at 75° C. for 16 h to obtain a carbon-based magnetic hydrogel; the amount of the graphene dispersion is 20 mL, and the concentration of the graphene oxide dispersion is 2 mg / mL; the amount of the dopamine hydrochloride solution is 20 mL, and the concentration of the dopamine hydrochloride solution is 2 mg / mL; the amount of the ferroferric oxide precursor solution is 40 mL, and the mass ratio of ferric chloride to ferrous chloride in the ferroferric oxide precursor solution is 2:1;
[0146] (7) Ammonia water was added dropwise to the carbon-based magnetic hydrogel obtained in step (6) until the pH value was 9, and then washed with an ethanol aqueous solution with a mass concentration of 20% until the pH value was 7, the ethanol aqueous solution was extracted, and finally pre-frozen at -20°C for 72 hours and freeze-dried at -40°C for 72 hours to obtain a carbon-based magnetic aerogel.
[0147] The carbon-based magnetic aerogels prepared in Test Examples 11 to 13 were observed by scanning electron microscopy, and the obtained SEM images are as follows: Fig.17 As shown. Fig.17 It can be seen that when DGA (graphene oxide): Fe 3+ (i.e. ferric chloride): Fe 2+ When the mass ratio of graphene oxide: ferric chloride: ferrous chloride is 2:4:2, the particle size distribution in the carbon-based magnetic aerogel is relatively dispersed and uniform, while when the concentration is too small (i.e. 2:2:1), the particle distribution is very small, and when the concentration is too large (i.e. 2:6:3), agglomeration and coating will occur. Therefore, the concentration when the mass ratio of graphene oxide: ferric chloride: ferrous chloride is 2:4:2 is selected as the optimal value of carbon-based magnetic aerogel.
[0148] The properties of the carbon-based magnetic aerogel / graphene nylon composite fabric prepared in Example 1 were tested and tested by electron microscopy. The electron microscopy images obtained are as follows: Fig.18 As shown. Fig.18 It can be seen that in the carbon-based magnetic aerogel / graphene nylon composite fabric provided by the present invention, graphene is evenly distributed on the composite fabric, and magnetic particles are also distributed on it, thereby improving the electromagnetic shielding effectiveness of the composite fabric. According to the window method recorded in GJB6190-2008 "Measurement Method for Shielding Effectiveness of Electromagnetic Shielding Materials", the electromagnetic shielding effectiveness of the carbon-based magnetic aerogel / graphene nylon composite fabric was tested, and it was found that the electromagnetic shielding effectiveness of the carbon-based magnetic aerogel / graphene nylon composite fabric was 36.4-48.3dB at high frequency points, which has a certain electromagnetic shielding effectiveness, far exceeding the GB T 26667-2011 application standard for civil electromagnetic shielding materials.
[0149] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a carbon-based magnetic aerogel / graphene nylon composite fabric, comprising the following steps: (1) mixing an electromagnetic shielding fabric, a graphene dispersion, a dopamine hydrochloride solution and a ferroferric oxide precursor solution, and then performing a hydrothermal reaction to obtain a carbon-based magnetic hydrogel containing the fabric; the electromagnetic shielding fabric is an electromagnetic shielding three-dimensional fabric or an electromagnetic shielding honeycomb fabric; (2) freeze-drying the carbon-based magnetic hydrogel containing fabric obtained in step (1) to obtain a carbon-based magnetic aerogel composite fabric; (3) The carbon-based magnetic aerogel composite fabric obtained in step (2) is mixed with an aqueous polyurethane solution and then cured to obtain a carbon-based magnetic aerogel / graphene nylon composite fabric.
2. The preparation method according to claim 1, characterized in that: When the electromagnetic shielding fabric in step (1) is an electromagnetic shielding three-dimensional fabric, the three-dimensional structure of the electromagnetic shielding three-dimensional fabric is through-orthogonal, layered orthogonal, through-angle interlocking or layered angle interlocking.
3. The preparation method according to claim 1, characterized in that: The electromagnetic shielding fabric in step (1) is woven from graphene nylon filaments; the specification of the graphene nylon filaments is 300D / 144F.
4. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of graphene oxide in the graphene oxide dispersion to dopamine hydrochloride in the dopamine hydrochloride solution is 1:(0.5-2).
5. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of graphene oxide in the graphene oxide dispersion and the mass ratio of ferric chloride to ferrous chloride in the ferrosoferric oxide precursor solution is 2:4:
2.
6. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction in step (1) is 70 to 80° C., and the time of the hydrothermal reaction is 12 to 20 hours.
7. The preparation method according to claim 1, characterized in that: The viscosity of the aqueous polyurethane solution in step (3) is less than 300 mPa·S.
8. The preparation method according to claim 1, characterized in that: The curing temperature in step (3) is 60 to 90° C. and the curing time is 6 to 8 hours.
9. The carbon-based magnetic aerogel / graphene nylon composite fabric prepared by the preparation method according to any one of claims 1 to 8.
10. Use of the carbon-based magnetic aerogel / graphene nylon composite fabric according to claim 9 in electronic devices.
Citation Information
Patent Citations
Graphene-melamine foam aerogel and preparation method thereof
CN106000366A
Preparation method of magnetic graphene aerogel
CN107140620A
Novel multifunctional three-dimensional conduction fabric, preparation method thereof and application of fabric
CN109652898A
Electromagnetic shielding composite material and preparation method thereof
CN112709079A
Preparation method of Fe3O4 / rGO / polyimide aerogel electromagnetic wave-absorbing material
CN114752101A
Cited By
Method for testing electromagnetic shielding performance of conductive nano chinlon fabric material
CN121522275A
Method for testing electromagnetic shielding performance of conductive nanometer nylon fabric material
CN121522275B